Metabolic features of myeloma cells in the context of bone microenvironment: Implication for the pathophysiology and clinic of myeloma bone disease - Raimondi, Vincenzo; Toscani, Denise; Marchica, Valentina; Burroughs-Garcia, Jessica; Storti, Paola; Giuliani, Nicola (Frontiers in Oncology, 2022)
Multiple myeloma (MM) is a hematological malignancy characterized by the accumulation of malignant plasma cells (PCs) into the bone marrow (BM). The complex interaction between the BM microenvironment and MM PCs can lead to severe impairment of bone remodeling. Indeed, the BM microenvironment exerts a critical role in the survival of malignant PCs. Growing evidence indicates that MM cells have several metabolic features including enhanced glycolysis and an increase in lactate production through the upregulation of glucose transporters and enzymes. More recently, it has been reported that MM cells arehighly glutamine addicted. Interestingly, these metabolic changes in MM cells may affect BM microenvironment cells by altering the differentiation process of osteoblasts from mesenchymal stromal cells. The identification of glutamine metabolism alterations in MM cells and bone microenvironment may provide a rationale to design new therapeutic approaches and diagnostic tools. The osteolytic lesions are the most frequent clinical features in MM patients, often characterized by pathological fractures and acute pain. The use of the newer imaging techniques such as Magnetic Resonance Imaging (MRI) and combined Positron Emission Tomography (PET) and Computerized Tomography (CT) has been introduced into clinical practice to better define the skeletal involvement. Currently, the PET/CT with 18F-fluorodeoxyglucose (FDG) is the diagnostic gold standard to detect active MM bone disease due to the high glycolytic activity of MM cells. However, new tracers are actively under investigation because a portion of MM patients remains negative at the skeletal level by 18F-FDG. In this review, we will summarize the existing knowledge on the metabolic alterations of MM cells considering their impact on the BM microenvironment cells and particularly in the subsequent formation of osteolytic bone lesions. Based on this, we will discuss the identification of possible new druggable targets and the use of novel metabolic targets for PET imaging in the detection of skeletal lesions, in the staging and treatment response of MM patients.